The impact of social support on anxiety among college students majoring in preschool education : The mediating role of psychological resilience - Jie, Shi; Siok Ping, Voon (Arts and Science Press Pte. Ltd, 2025)
Since the end of the COVID-19 pandemic, many studies have shown that the anxiety level of college students has increased, but there are few studies on the sample of students majoring in preschool education, and the results show that the anxiety level is higher than that of college students in other majors. The basic position of preschool education in the national education system and the integrated training system of preschool teachers make us pay attention to the students of preschool education. The purpose of this study is to study the anxiety status and relieving mechanism of pre-school students. This study is a cross-sectional study design, using an online questionnaire survey method. SPSS 21.0 and its plug-in PROCESS were used to process the data of anxiety, social support and psychological resilience of 971 subjects. The results show that anxiety is negatively correlated with social support and mental toughness, while social support and mental toughness are positively correlated; psychological resilience plays a completely mediating role between social support and anxiety. This study has enriched the research on the mental health level of students majoring in preschool education, and provided guidance for the psychological counseling of students in the school mental health center, which has theoretical significance